Vol.1 - Lal, A.K.(ed.) (New Delhi, 2003)
The festschrift in honour of Dr. Bindeshwar Pathak, the inaugural figure of sanitation movement in India, seeks to continue the dialogue on possibilities and constraints of change in a social setting traditionally unfavourable to radical social transformation. The ramifications of interaction of the social context with the initiatives for development and change constitute the themes accorded treatment in depth as well as in coverage in the papers especially prepared for inclusion. Experiences encountered in the wake of unleashing of forces wedded to removal of inequalities traditionally embedded as well as recently induced have been elaborated to locate the degree and direction of change. Initiatives and measures contemplated to reduce the imbalances produced and deficits left unattended have been accorded special treatment. Unease of sections aspiring for accommodation in the emerging opportunity structure is discussed to find out effective strategies for inclusion of the excluded. Structures and strategies of domination are discussed to detail the implications of interaction between forces of change and stagnation. Widening growth disparities are taken note of to recommend transformation of social and economic structure.
Essays in Honour of Dr. Bindeshwar Pathak
Keywords: Social change-India